Analisis Strategi Penghimpunan dan Pendistribusian Infak dan Sedekah Pada Lembaga Arifin Pilar Gemilang Insani - Harun, Muhammad; Rudianto, Asep; Suryaman, Maman (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The wealth that a person has is a trust, and people who have wealth have more opportunities to do good deeds, namely alms and alms. it is to meet the needs of the students of the illustrious Human Pillar Foundation. In managing alms and alms money, a strategy is needed to develop alms money in its collection and distribution so that it can be utilized as much as possible. Anfak means spending part of the property or income / income for a benefit ordered by Islamic teachings. Sadaqah is giving something without any reward because it only expects the pleasure and reward of God Almighty. Fund raising is the business activity of financial institutions in attracting and collecting money from the public and absorbing it in the form of deposits, demand deposits and other securities deposits. Distribution is the distribution of goods to many people or to several places. Strategy is a comprehensive approach related to the idea, planning, and implementation of an activity. In conducting this research, the author used descriptive qualitative methods, and data sources were obtained using two data sources, namely primary data and secondary data obtained from interviews, documentation, and literature reviews related to depth strategies and handout collection. Data collection techniques are observation, interview and documentation methods. The results of this study indicate that the collection strategies carried out are, charity funds, regular donors, branch trustee receivables, donor commitment, online alms by transfer. The distribution strategy implemented focuses on Hafez/Hafiza students at the Institute, namely to fulfill all the needs, needs and obligations of Institute students. Keywords: tunnels and leaflets; distribution; collection; strategy